2020
DOI: 10.3390/biom10030368
|View full text |Cite
|
Sign up to set email alerts
|

Tiny but Fatty: Lipids and Fatty Acids in the Daubed Shanny (Leptoclinus maculatus), a Small Fish in Svalbard Waters

Abstract: The seasonal dynamic of lipids and their fatty acid constituents in the lipid sac and muscles of pelagic postlarval Leptoclinus maculatus, an ecologically important fish species in the Arctic food nets, in Kongsfjord, Svalbard waters was studied. The determination of the qualitative and quantitative content of the total lipids (TLs), total phospholipids (PLs), triacylglycerols (TAGs), cholesterol (Chol), cholesterol esters (Chol esters) and wax esters was analyzed by TLC, the phosphatidylserine (PS), phosphati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 54 publications
1
35
0
Order By: Relevance
“…), the relevant functioning of membranes is secured by controlling their thickness, fluidity, and resistance to mechanical impacts (during high protein activity), as well as by implementing the thermal insulation function for membrane-bound enzymes in certain lipid bilayer domains. Thus, the results obtained in this study, as well as earlier [ 11 ], regarding the FA status of deep-water fish in northern seas agree with the previously formulated concept of the functions of polyunsaturated chains [ 89 , 90 , 91 ]: the configuration of FAs in lipids defines the properties, functions, and biological effects of the respective lipids in the organism.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…), the relevant functioning of membranes is secured by controlling their thickness, fluidity, and resistance to mechanical impacts (during high protein activity), as well as by implementing the thermal insulation function for membrane-bound enzymes in certain lipid bilayer domains. Thus, the results obtained in this study, as well as earlier [ 11 ], regarding the FA status of deep-water fish in northern seas agree with the previously formulated concept of the functions of polyunsaturated chains [ 89 , 90 , 91 ]: the configuration of FAs in lipids defines the properties, functions, and biological effects of the respective lipids in the organism.…”
Section: Discussionsupporting
confidence: 92%
“…More recently, researchers [ 11 ] found that lipid unsaturation in arctic fish was primarily maintained by means of DHA and EPA. This is related to the organism’s locomotor activity under certain conditions (pressure, temperature, currents, etc.)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations